Branched Bi2S3/TiO2 nano-heterostructure with enhanced photoelectric performance. (15th November 2019) - Ning, Xiangmei; Huang, Jinliang; Li, Lihua; Gu, Yongjun; Jia, Shuguo; Qiu, Ranfeng; Kim, Bok H
Abstract: The fabrication of a branched nano-heterostructure composed of Bi2 S3 nanosheet branches and TiO2 nanorod stem was performed using a facile and cost-effective hydrothermal method. The nanoscale morphology of Bi2 S3 deposited on TiO2 nanorod arrays was regulated by controlling the hydrothermal growth time of Bi2 S3 sensitizer. The optical properties and photoelectrochemical performance were evaluated systematically for Bi2 S3 /TiO2 heterostructures with different morphology. The Bi2 S3 /TiO2 heterostructures presented the higher visible-light absorption ability and photoelectric performance compared to the bare TiO2 . The highest photocurrent density of approximately 6.01 mA cm −2 was obtained for the Bi2 S3 /TiO2 heterostructure with 1 h hydrothermal sensitization time. The improved photoelectric performance was attributed to the unique branched structure resulting in an obviously enhanced light absorption in visible-light region and better electron-hole separation and transporation.